Accelerating optimization of IN718 by mapping alloying effects on phase stabilities and mechanical properties using high-throughput calculations - Z.Y. Xiong (Materials & Design, 2022)
The premature failure of the γ’’-strengthen mechanism restricts the further application of Inconel 718 superalloys at temperatures over 650 °C. Although numerous attempts have been made to improve the performance, the complex chemical composition and phase constitution still pose a great challenge to the development of IN718. We systematically explore the sole/synergetic effect of various alloying elements on stabilities of the matrix (γ) and the precipitates (γ’, γ’’) in IN718, and map their mechanical properties versus chemical compostions by employing high-throughput calculations. Results indicate that the promotive effect of Al and Ti on stability of γ’ phase exhibits a synergistic relationship, either over-low Al or Ti would obviously weaken the promotion. W is detrimental to stability of γ’ phase. Co yields a complicated effect on stabilities that depends on its sublattice position and the Al and Ti contents. By drawing the mechanical maps, it shows that the preferred composition range for the phases with desired properties is roughly demarcated in theory. The Al, Ti, and Nb concentrations need to be cautiously altered due to their conflicting effects on stabilities and mechanical properties of the phases. Alloying Co is encouraged to enhance the properties while alloying W might be theoretically deprecated.